1999
DOI: 10.1103/physreve.59.2853
|View full text |Cite
|
Sign up to set email alerts
|

Level spacings at the metal-insulator transition in the Anderson Hamiltonians and multifractal random matrix ensembles

Abstract: We consider orthogonal, unitary, and symplectic ensembles of random matrices with (1/a)(ln x) 2 potentials, which obey spectral statistics different from the Wigner-Dyson and are argued to have multifractal eigenstates. If the coefficient a is small, spectral correlations in the bulk are universally governed by a translationally invariant, one-parameter generalization of the sine kernel. We provide analytic expressions for the level spacing distribution functions of this kernel, which are hybrids of the Wigner… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
42
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 59 publications
5
42
0
Order By: Relevance
“…An exact expression for the two level critical spectral function was conjectured in [16] for orthogonal and symplectic ensembles. In the context of the Anderson model, a similar result was conjectured by Nishigaki [10].…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…An exact expression for the two level critical spectral function was conjectured in [16] for orthogonal and symplectic ensembles. In the context of the Anderson model, a similar result was conjectured by Nishigaki [10].…”
Section: Introductionsupporting
confidence: 70%
“…Recently, new random matrix ensembles [1,2,3,4,5,6,7,8] depending on additional parameters have been proposed to describe spectral correlations in this critical case. These new models for critical statistics have been successfully utilized to describe the spectral correlations of a disordered system at the Anderson transition in three dimensions [9,10], two dimensional Dirac fermions in a random potential [11], the quantum Hall transition [12] and of the QCD Dirac operator in a liquid of instantons [13,7].…”
Section: Introductionmentioning
confidence: 99%
“…(4.3) is a natural extension of the Painlevé V type equation [13] derived for the resolvent of the sine kernel (2.5) at a = 0. One of the authors (SMN) then confirmed that the LSDs at the mobility edge are well fitted, with a single tunable parameter a, to these analytic formulas from the deformed kernel (blue curves in Fig.2) for three symmetry classes [36]. The χ 2 /dof of the fitting in the range 0 ≤ s ≤ 5 (with bin-size 0.05) is as small as 0.23 (orthogonal) and 0.…”
Section: Pos(lattice 2013)018mentioning
confidence: 66%
“…Entrusting that these universality among three different ensembles [34] to be an indication of uniqueness of multifractal deformation of the classical random matrices, one of the authors (SMN) computed the LSDs of Ensemble I in three symmetry classes [35,36] (Fig.3). Ensemble I is…”
Section: Pos(lattice 2013)018mentioning
confidence: 99%
“…(25-27) with the kernel Eq. (28) give the same leading terms as Eqs. (13-15) with G(s, 0) given by Eq.…”
mentioning
confidence: 89%